Peran Financial Self-Efficacy dalam Memediasi Pengaruh Social Comparison Orientation dan Financial Literacy terhadap Financial Management Behavior Generasi Z di Jepara - Devi Atalia Zahra; Vicky Oktavia; Diana Puspitasari; Yenny Ernitawati (Jurnal Multidisiplin Indonesia, 2026)
This research explores financial self-efficacy as a mediator in the influence of social comparison orientation and financial literacy on the financial management behavior of Generation Z in Jepara. Data from 140 purposively selected respondents were analyzed using the PLS-SEM approach (SmartPLS 4.0) to examine the direct and indirect effects between variables via path analysis. The results showed that Financial Literacy has a positive and significant effect on both Financial Self-Efficacy and Financial Management Behavior. In addition, Financial Self-Efficacy also has a positive and significant effect on Financial Management Behavior. Social Comparison Orientation was proven to have a positive and significant effect on Financial Management Behavior, but it does not have a significant effect on Financial Self-Efficacy. Financial Self-Efficacy was proven It can mediate the influence of Financial Literacy on Financial Management Behavior, but it cannot mediate the influence of Social Comparison Orientation on Financial Management Behavior. So, it’s proven that Financial Literacy and Financial Self-Efficacy play an important role in improving Financial Management Behavior among Generation Z in Jepara behavior among Generation Z in Jepara is influenced by financial knowledge and Financial Self-Efficacy.